1999
DOI: 10.1054/jhsb.1998.0183
|View full text |Cite
|
Sign up to set email alerts
|

Blatt’s Capsulodesis for Chronic Scapholunate Dissociation

Abstract: We have reviewed prospectively 44 cases of chronic scapholunate dissociation treated by Blatt's dorsal capsulodesis. The diagnosis was based on clinical and arthroscopic criteria. The minimum follow-up was 2 years. The results were analysed clinically and radiologically. Postoperatively statistically significant reductions in wrist movements and grip strengths were noted. Delay in surgery and presence of compensation claims were also statistically significant factors. Patients with a high column/row index had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 11 publications
4
53
0
7
Order By: Relevance
“…Subsequent studies by Moran et al [34] and Deshmukh et al [16] supported Wyrick's findings. At both short-term and intermediate follow-up, the range of motion for the flexion extension arc was decreased to 60-70 % of the unaffected side.…”
Section: Stage 4: Complete Disruption With Irreparable Ligament and Rmentioning
confidence: 76%
“…Subsequent studies by Moran et al [34] and Deshmukh et al [16] supported Wyrick's findings. At both short-term and intermediate follow-up, the range of motion for the flexion extension arc was decreased to 60-70 % of the unaffected side.…”
Section: Stage 4: Complete Disruption With Irreparable Ligament and Rmentioning
confidence: 76%
“…Static SL dissociation was seen on the left side in 2 patients and on the right side in 10 patients. The time from injury to surgery averaged 8 months (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The average follow-up period after surgery was 15.8 months (range: 13-34).…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports on capsulodesis are divided between those which reproduced the good results reported by Blatt (1987), those which obtained poor results and those which suggested that capsulodesis should be used in selected patients who fulfil certain criteria (Table 3). These criteria include less than 1 to 2 years since injury, no compensation claim, not involved in heavy labour, a scapholunate angle of less than 701, a scapholunate gap less than 5 mm and a high column/row index (Deshmukh et al, 1999;Wyrick et al, 1998). While the majority of our patients had a scapholunate angle of less than 701 and a scapholunate gap of less than 5 mm, we did not measure the column/ row index and did not find that the other criteria affected the outcome in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…of patients Results ROM Recommendation Lavernia et al (1992) 21 9 (1.4) (Patient satisfaction) à Only flexion reduced Treatment of choice Deshmukh et al (1999) 44 39% satisfied All movements reduced Only on selected patients Wyrick et al (1998) 17 12% good or excellent results All movements reduced to 60% Should not be done Wintman et al (1995) 18 7.5 (2.9) (Patient satisfaction) Ãà Only flexion reduced Treatment of choice Konduru et al (2005) 20 85% satisfied Flexion and radial deviation reduced Treatment of choice à Patient satisfaction on a scale of 0 (extremely unhappy) to 10 (extremely happy).…”
Section: Authorsmentioning
confidence: 99%